MONITORING PERALATAN BERBASIS QR CODE PADA PEMBELAJARAN DI LABORATORIUM - Hilda Ashari; Muhammad Iswal Burhan (Pandega: Jurnal Kajian Pendidikan dan Kepramukaan, 2023)
This research is an R&D (Research and Development) study that aims to produce the development of a tool lending information system using an android-based QR code in the Pendidikan Teknik Elektro department laboratory. As well as to determine the feasibility of borrowing equipment applications using an android-based QR Code. This research uses the SDLC development method, with a development model, namely prototyping. Research data obtained by questionnaire and documentation techniques. Based on the results of the research, an equipment loan application using an android-based QR code was obtained in the Electrical Engineering Education laboratory, Faculty of Engineering, Makassar State University, which is an android mobile-based application. Furthermore, testing this application using the blackbox method shows that the loan application function runs well, and through the application validation trial stage with a percentage of feasibility conducted by two validators, namely 32 with a percentage of 100%, so it can be concluded that the application developed is very feasible.